Theoretical study of dual-core photonic crystal fibers with metal wire - Zhang, Shuyan (2013)
In this paper, we, for the first time, systematically study a new structure of a dual-core photonic crystal fiber filled with a metal wire in the center air hole. Theoretical analysis based on the supermode theory and the coupled-mode theory shows that the directional power transfer between the two fiber cores is enhanced by the resonant coupling between the surface plasmon modes and the fiber core-guided modes. A coupling length reduction of more than one order of magnitude is demonstrated for the new structure in the near-infrared regime. As a new fiber coupler device, the highest coupling efficiency is 81.82%, the insertion loss is as low as 0.87 dB, and the extinction ratio is 30.54 dB at 1550 nm for the optimized design configuration. The new structure is compact in size and easy to fabricate, making it promising for miniaturized complex communication devices.